SCN1A and Its Related Epileptic Phenotypes - Sullo, Federica; Pasquetti, Elisa; Patanè, Francesca; Lo Bianco, Manuela; Marino, Simona D.; Polizzi, Agata; Falsaperla, Raffaele; Ruggieri, Martino; Zanghì, Antonio; Praticò, Andrea D. (Journal of Pediatric Neurology, 2021)
Epilepsy is one of the most common neurological disorders, with a lifetime incidence of 1 in 26. Approximately two-thirds of epilepsy has a substantial genetic component in its etiology. As a result, simultaneous screening for mutations in multiple genes and performing whole exome sequencing (WES) are becoming very frequent in the clinical evaluation of children with epilepsy. In this setting, mutations in voltage-gated sodium channel (SCN) α-subunit genes are the most commonly identified cause of epilepsy, with sodium channel genes (i.e., SCN1A, SCN2A, SCN8A) being the most frequently identified causative genes. SCN1A mutations result in a wide spectrum of epilepsy phenotypes ranging from simple febrile seizures to Dravet syndrome, a severe epileptic encephalopathy. In case of mutation of SCN1A, it is also possible to observe behavioral alterations, such as impulsivity, inattentiveness, and distractibility, which can be framed in an attention deficit hyperactivity disorder (ADHD) like phenotype. Despite more than 1,200 SCN1A mutations being reported, it is not possible to assess a clear phenotype–genotype correlations. Treatment remains a challenge and seizure control is often partial and transitory.
Keywords: SCN1A; sodium channel; Dravet syndrome; febrile seizures; epilepsy